2008
DOI: 10.1160/th08-03-0187
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel mutation in the von Willebrand factor propeptide in a distinct subtype of recessive von Willebrand disease

Abstract: von Willebrand factor (VWF) is a plasma protein that consists of a series of multimers of which the high-molecular-weight VWF multimers are the most potent in platelet adhesion and aggregation. The propeptide of the VWF (VWFpp) is known to be essential in the process of multimer assembly. Genetic studies were performed in a patient with a phenotype of von Willebrand disease (VWD) characterized by very low plasma factor VIII and VWF levels and a VWF consisting of only a dimeric band and total absence of all mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…The laboratory phenotype in patients with recessive VWD type 2C (2A subtype IIC) varies widely from severe (with very low levels of FVIII:C and VWF:Ag, unmeasurable VWF:RCo, absent RIPA and strongly prolonged BT as documented in five kindreds [6,7,8, 12, 15]) to rather mild VWD type 2C (with normal values for FVIII:C and VWF:Ag, low levels for VWF:RCo and VWF:CB and prolonged BT as reported in two kindreds [1, 11, 14]). The combination of a null mutation and a missense mutation in the D1 domain may mimic severe VWD type 3 [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The laboratory phenotype in patients with recessive VWD type 2C (2A subtype IIC) varies widely from severe (with very low levels of FVIII:C and VWF:Ag, unmeasurable VWF:RCo, absent RIPA and strongly prolonged BT as documented in five kindreds [6,7,8, 12, 15]) to rather mild VWD type 2C (with normal values for FVIII:C and VWF:Ag, low levels for VWF:RCo and VWF:CB and prolonged BT as reported in two kindreds [1, 11, 14]). The combination of a null mutation and a missense mutation in the D1 domain may mimic severe VWD type 3 [5].…”
Section: Discussionmentioning
confidence: 99%
“…In retrospect, the multimeric pattern of the VWD patients homozygous for R273W and C570S clearly showed the absence of high-molecular-weight multimers and a pronounced dimeric band consistent with type 2C (2A subtype IIC) VWD [6, 10]. In addition, expression studies of recombinant R273W, W377C and C570S showed secretion of VWF mainly consisting of dimers which failed to form intermediate- and high-molecular-weight multimers consistent with the clinical diagnosis of VWD 2C (2A subtype IIC) [6,7,8]. These findings indicate that mutations in the D1 and D2 VWFpp region completely abolish multimerization of VWF.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…After 24 hrs of incubation with serum free medium, cells were stimulated with phorbol-12-myristate-13-acetate (PMA, Sigma–Aldrich, St Louis, MO) at 500 nM for 1 hr or with histamine 100 µM (Sigma-Aldrich) [34] for 15 min, alternatively with estradiol 1 nM (Sigma-Aldrich) [35] for a further 24 hrs. As a positive control for cell stimulation VWF release was measured in cell media by ELISA as described [36]. Of the stimulants used, only histamine exhibited a 2-fold increase in VWF release.…”
Section: Methodsmentioning
confidence: 99%
“…The level of endogenous VWF in the GBM was measured by enzyme-linked immunosorbent assay (ELISA) as previously described (Lanke et al, 2008). Levels of ADAMTS13 (Cloud-Clone Corp, Houston, TX), elastase (Hycult Biotech, Uden, Holland), cathepsin G (Nordic BioSite, Täby, Sweden) and MMP9 (R&D Systems, Minneapolis, MN) were measured by ELISA kits according to the manufacturers' protocols.…”
Section: Methodsmentioning
confidence: 99%